Emissão de gases de efeito estufa na cultura da cana-de-açúcar sob diferentes sistemas de preparo do solo e doses de nitrogênio - Moro, Vagner João (2012)
Brazil is the world's largest producer of sugarcane. However, few studies have been conducted to evaluate the effect soil management systems and fertilization practices on emissions of greenhouse gases (GHG). Therefore, the present study was aimed to assess the GHG emissions during the life cycle of sugarcane under different soil management systems and nitrogen (N) fertilization. The study was comprised of two experiments. In the first experiment, four tillage systems (conventional tillage - CT; chisel plough - CP, No tillage - NT, and compacted No tillage - CNT) while in the second experiment different doses of N (0, 40, 80 and 120 kg N ha-1) were evaluated for their effect on GHG and productivity. GHG emissions were assesses on different dates and soil samples were also taken to measure the levels of mineral N and soil moisture. The global warming potential (GWP) in each management system was calculated by using initial and final C content of the soils plus the emissions of N2O and CH4 during the experiments. The sugarcane yield and CH4 emission (mean -1.25 kg CH4-C ha-1) were not affected by different tillage systems. The cumulative amount of CO2 varied in the following order: CT> NT> CP> CNT. In the CNT, greater flows of N2O after rainfall events was occurred which were approximately two times greater than the CT and CP (517 vs 254 μg m-2h-1) and 7.5 times higher than in NT. The CT tillage system showed higher value of GWP, followed by the CP and CNT indicating that the use of conservation tillage is a strategy with the potential to mitigate GHG emissions from sugarcane crop in southern Brazil. The N2O emission increased linearly with the doses of N applied. On an average, 0.28 kg N2O-N ha-1 was emitted from 20 kg N ha-1. The values of N2O emission factors were calculated based on IPCC methodology for the conditions of this study indicate that for doses less than 40 kg N ha-1 values obtained are below the default value of 1.25%. For doses above 60 kg N ha-1 values obtained are similar to the factors indicated by the IPCC. Emission factors based on the relationship between the N2O emission and productivity indicated that productivity was increased with doses above 40-60 kg N ha-1 with high amount of N2O emission per Mg produced.